PERLINDUNGAN HUKUM PEKERJA HARIAN LEPAS AKIBAT KECELAKAAN KERJA (STUDI PADA PENGEMUDI ANGKUTAN KOTA DI KOTA AMBON) - Evy Safitri Gani (IAIN Ambon, 2020)
All workers must be protected by the State, whether they are permanent workers, contract workers or casual daily workers. In practice, there are many casual daily laborers who do not make written agreements with employers or employers. Often they don't even know what their rights and obligations are. One of them is casual daily labor such as Ambon City public transport drivers. In carrying out his daily profession, the driver often works beyond work time. This was done to pursue deposits that must be given to public transportation entrepreneurs and a small amount of money to fulfill their daily needs. That's when they often do not care about health problems. Many work accidents occur as a result of that. Many parties can actually provide protection to urban transportation drivers in Ambon city, namely the Ambon City Transportation Office, BPJS Health and BPJS Employment. But sometimes it is often constrained because of the obstacles experienced by both workers, employers and the government. Keywords: legal protection, freelance, work accident